Notes per a una lectura de l'obra de Joan Fuster - Riera, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
This study suggest reading Joan Fuster's work from a formal point of view, considering this reasonings, expressive resources and syntax. It alto presents a diachronic proposal as far as topics, variety of texts and thinking of the writer from Sueca are concerned.